Hubungan Kebiasaan Olahraga dan Pola Makan dengan Kejadian Hipertensi pada Lansia - Rahmawati, Dina; Firdaus, Muhamad Beril (Universitas Faletehan, 2023)
The prevalence of hypertension in elderly continues to increase annually. Hypertension in elderly is influenced by biological changes that occur in old age and other factors, including poor exercise habits and unhealthy dietary patterns. The aim of this study was to determine the correlation between poor exercise habits and unhealthy dietary patterns with the occurrence of hypertension in elderly. This research adopted a cross-sectional approach with 89 respondents selected through purposive sampling method. The analysis results showed that 50 respondents (56.2%) had poor exercise habits, 53 respondents (59.6%) experienced hypertension, and 59 respondents (66.3%) had an unhealthy dietary pattern. The bivariate analysis revealed a significant relationship between dietary patterns (p value 0.013) and exercise habits (p value 0.000) with the occurrence of hypertension in elderly. Therefore, to prevent hypertension in elderly, an appropriate education and intervention were needed to enhance awareness and promote healthy behaviors among elderly with the hope of reducing the risk of hypertension.